2003
DOI: 10.1002/anie.200250507
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Stereocontrolled Entry to the ABCD Tetracyclic Core of Neotuberostemonine

Abstract: Four out of the five rings of the alkaloid neotuberostemonine (1) are present in the advanced precursor 2. The tetracyclic compound 2 has now been prepared in a short, linear route via lactone acid 3. A key step in the synthesis was the cuprate‐mediated SN2′ ring‐opening desymmetrization of the C2‐symmetric bislactone 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The rearrangement leads to the tricycle 40 in high yields. This motif is found as a core structure in various alkaloids such as neotuberostemonine, stenine, and tuberostemonine (Figure ) . The reaction also provides a versatile approach to bi- or tricyclic derivatives of perhydroazaazulene .…”
Section: 12 Formation Of Four-membered Heterocyclesmentioning
confidence: 98%
“…The rearrangement leads to the tricycle 40 in high yields. This motif is found as a core structure in various alkaloids such as neotuberostemonine, stenine, and tuberostemonine (Figure ) . The reaction also provides a versatile approach to bi- or tricyclic derivatives of perhydroazaazulene .…”
Section: 12 Formation Of Four-membered Heterocyclesmentioning
confidence: 98%
“…Previously, we reported that N -pentenyl-substituted maleimide derivatives 1 undergo an efficient formal [5 + 2] cycloaddition reaction on UV irradiation . The reaction has proved to be general for a range of maleimide derivatives and has recently been used by us as a key step in alkaloid synthesis . The reaction is related to similar photochemistry described by Mazzocchi 3 for phthalimide derivatives and is thought to proceed by initial [2 + 2] cycloaddition to form the zwitterion 2 , which then undergoes fragmentation to the azepine 3 (Scheme ).…”
mentioning
confidence: 96%
“…This group has very recently been able to modify their approach to deliver the first total synthesis of (±)-neostenine 5 . In 2001, we embarked on a program to deliver neotuberostemonine 6 by a strategy that was to proceed via the use of an oxo derivative of neostenine 5 as an advanced intermediate . At the time, 5 had not been identified, but following its isolation in 2003 it was evident that it would be within reach of our ongoing route to 6 .…”
Section: Introductionmentioning
confidence: 99%